Work Effectiveness Examined through the Aspects of Workload and Burnout - Retnowati, Eli; Hariani, Mila; Irfan, Moch.; Darmawan, Didit; Putra, Arif Rachman; Anjanarko, Tri Seno; Munir, Misbachul (Universitas Sahid, 2023)
This study aims to examine the influence of workload and burnout on employee work effectiveness. It employs a quantitative method with data collection through questionnaires. The research methodology involves data collection through questionnaires distributed to 120 employees of PT ABC in Gresik City. The sampling technique employed is saturation sampling, involving all employees of PT ABC in Gresik City. Regression analysis is utilized to test the relationship between workload and burnout variables on employee work effectiveness. The results of this study indicate a significant relationship between workload and burnout and employee work effectiveness. The higher the workload borne by employees, the higher the likelihood of experiencing burnout, which ultimately has a negative impact on their work effectiveness